O desejo de viver belas histórias: uma investigação existencial, hermenêutica e romanesca sobre identidade pessoal - Costa, Vítor Hugo dos Reis (2021)
The present study intends to carry out an investigation of a device for structuring personal identities that will be called the desire to live beautiful stories. Inspired by Jean-Paul Sartre's phenomenological ontology notion of desire of being presented in Being and Nothingness, the idea of the desire to live beautiful stories is configured in a historical and narrative modulation of the desire to be, a modulation in which individuals do not they assume the possession of essential identities but the possibility of realizing these identities through time. The exploration of the theme will therefore have four moments. The first will consist of the interpretative reconstruction of Jean- Paul Sartre's existential philosophy and, in particular, of philosophical anthropology centered on the idea of freedom that is deduced from the combination of phenomenological ontology and existential psychoanalysis offered in Being and Nothingness. The second moment will consist of the presentation of elements of narrative hermeneutics and, in particular, the ideas about narrative identity of the philosopher Paul Ricoeur in Time and narrative and Self as another. The intention will be to show that the hermeneutics of the self functions as an unavoidable extension of existential psychoanalysis in tracking the desire to live beautiful stories. The third step will be to investigate the plausibility of the proposal for a graft of narrative hermeneutics in existential psychoanalysis and will consist especially of the analysis of a case of intellectual trajectory through the world of philosophy and politics: the trajectory of Jean-Paul Sartre. It is intended to show how the narrative identity can be configured as a collection of stories and episodes and escape the requirement of a life's narrative unity. In the fourth and last moment of this study, we intend to show how the art of the novel offers itself in a privileged way as a means of observing human possibilities. Centered on examining Milan Kundera's novelistic and essayistic works, this final part of the study will show the historical link between art of the novel and modernity and the contributions and demands that the exploration of this link offer in the itinerary of the hermeneutical exploration of narratively elaborated existential themes.